Family dispute resolution: Characteristics of cases resolved by trial. (April 2021) - Poitras, Karine; Birnbaum, Rachel; Saini, Michael; Bala, Nicholas; Cyr, Francine
Highlights: Family separations that resolved by a trial are not common. Mediation, younger children, and resistance to contact are associated with a family trial. Allegations of domestic violence are not associated with family trial. Child resistance to contact is a priority conflict indicator to consider. Knowledge about factors associated with trial is needed to implement an effective triage system. Abstract: The vast majority of parental separations and divorces are resolved without resulting in a trial in family court, but the cases that proceed to trial have both higher financial and emotional costs for families. A better understanding of the factors associated with the use of a trial to resolve family disputes can assist the family justice system to develop triage models to identify these cases at an early stage,  and to provide resources to families to reduce the likelihood of a trial. A court file study was undertaken at two family courts in Québec, Canada. Of the total random sample (n = 987), 48 cases went to trial, revealing a low rate of trials in the family justice system, though one that is higher than in other Canadian jurisdictions. An additional oversampling of 100 court files that went to trial was completed to better understand the factors associated with trials. Multivariate logistic regression was used to identify factors associated with resolution of a case by a trial. Results show that 6 predictors variables were associated with a family trial: a temporary care motion; not having a joint application; representation of the respondent by a lawyer; younger children involved; child resistance to contact; and prior unsuccessful use of mediation services. These findings suggest the importance of the early identification of cases that are likely to result in trials based on the factors reported. Future research is required about the decision-making processes of parents, lawyers and judges for a better understanding of the pathways through the family justice process.